2014
DOI: 10.1186/1745-6215-15-374
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone- and internet-assisted self-management and adherence tools to manage Parkinson’s disease (SMART-PD): study protocol for a randomised controlled trial (v7; 15 August 2014)

Abstract: BackgroundNonadherence to treatment leads to suboptimal treatment outcomes and enormous costs to the economy. This is especially important in Parkinson’s disease (PD). The progressive nature of the degenerative process, the complex treatment regimens and the high rates of comorbid conditions make treatment adherence in PD a challenge. Clinicians have limited face-to-face consultation time with PD patients, making it difficult to comprehensively address non-adherence. The rapid growth of digital technologies pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Most of those systems are relatively invasive and time consuming and do not differentiate normal movement from tremor and high activity from dyskinesia . In the past few years, great interest has arisen in the use of smartphones application for the evaluation and treatment of patients with PD …”
Section: Discussionmentioning
confidence: 99%
“…Most of those systems are relatively invasive and time consuming and do not differentiate normal movement from tremor and high activity from dyskinesia . In the past few years, great interest has arisen in the use of smartphones application for the evaluation and treatment of patients with PD …”
Section: Discussionmentioning
confidence: 99%
“…Participants discussed multiple topics including beliefs about associations between weather and joint pain, existing views and experiences on the use of smartphones and other digital technologies, and views about recording symptoms for use in research. A preexisting health-monitoring smartphone app, designed by uMotif (a digital health company) and known to have high patient engagement [12], was then introduced using a brief film to prompt discussion and feedback [13]. Patients’ views were sought on the design, usability, and variables to be recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Adherence to prescribed treatment is necessary to achieve desired health outcomes; however, studies have shown that 30% – 50% of patients do not take medications as prescribed [913]. Non-adherence to medication for chronic conditions has been associated with poor treatment outcomes, including increasing hospitalization rates and health care costs [11, 12, 14]. Conversely, research has found a dose-response between treatment adherence and positive health outcomes [3, 4, 12, 15, 16].…”
Section: Introductionmentioning
confidence: 99%